SISTEM INFORMASI AKADEMIK & ASESMEN DALAM ANAK BERKEBUTUHAN KHUSUS PADA SLB MUTIARA BUNDA (Program Studi Teknik Informatika Universitas Muhammadiyah Cirebon, 2024)
Academic information systems & assessments in the development of children with special needs are data processing related to school academic information and assessment of children with special needs. The data processed is in the form of data on teachers, students, subjects, classes, grades management, and developmental assessments. From observations and interviews with teachers at SLB Mutaira Bunda Losari, it was found that the process of managing the academic system was still carried out manually. In producing all academic reports and the process of assessing student development it is felt that they are still not optimal and accurate and it is relatively long to complete the reports produced. Therefore, in this study, the authors created an academic information system & assessment for children with special needs that can help increase effectiveness in managing academic data and developmental assessments. The result of this research is an academic information system & assessment in children with special needs, users of this system consist of admins, teachers, homeroom teachers, assessors and students. This system can manage academic data and developmental assessments. With the implementation of this system, it is hoped that it will be able to assist teachers and assessors at Mutiara Bunda SLB in managing academic-related data and developmental assessment data so that it can reduce data recording errors that may occur in the running system and can minimize data loss and damage.